Witnessing the American Century : Via Berlin, Pearl Harbor, Vietnam, and the Straits of Florida - Brady, Capt. Allen Colby (Book collections on Project MUSE., 2019)
"The rise of Adolf Hitler, America's Great Depression in the heartland, the bombing of Pearl Harbor, American life following World War II, the Korean War, America's development of atomic weapons in the Cold War age, the Bay of Pigs Invasion and the Cuban Missile Crisis, the Vietnam War, and the Mariel boatlift. Captain Allen Brady not only witnessed all of these events but actually participated in them, in many instances as a US Naval Aviator. So many Americans and global citizens alike are not even aware of the importance of these pivotal moments; as generations age and pass on, without important accounts like this one, much is forgotten. More than just a memoir, Brady's book is an important document from one of the last of his generation, reminding us of the pivotal moments that should not be lost to history. Witnessing the American Century is Captain Brady's firsthand account of his incredible life, and his memories elucidate America's role in the most significant world events from the previous century."--Provided by publisher.